1933 Haw. Sess. Laws 38, § 9 - (:unkn) unknown (My University, 1933)
An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 9: Prohibited the alteration, removal, obliteration or the make, model, manufacturer's number, or other mark of identity of any firearm or ammunition. Prohibited possession of such firearms or ammunition. Violators fined not more than five hundred dollars or imprisoned not more than one year, or both fine and imprisonment.
Keywords: DEFACED FIREARMS